Pengaruh Kepercayaan, Pengetahuan dan Sikap Terhadap Akses Jamban Di Perkotaan - Mila Mardotillah; Budhi Gunawan; Rini S. Soemarwoto; Ardini S. Raksanagara (Institut Teknologi Sepuluh Nopember, 2019)
The difficult access of urban healthy latrines is influenced by populationdensity, limitation of infrastructure and high mobility. Cultural factors becomeone of the keys in influencing people behavior to access healthy latrines. Theaim this research was to explore the cultural factors influencing the people toaccess the healthy latrine. The method used was a retrospective quantitativeapproach with cross sectional analytical method (cross sectional) in order toknow the cultural factors that influence people behaviour in using healthylatrines. The research found that the cultural factors related to access ofhealthy latrines include belief on the taboo, gender, beliefs and differences ofeach generation. The significant influential factors are trust, knowledge andattitude. While other factors simultaneously affect the citizen in behavingtoward using healthy latrines. The conclusion was that the behaviour inaccessing healthy latrines is created by individual’s knowledge, attitudes andactions. The behaviour will be established and successful if the cultural factorapproach is carried out simultaneously. The individual’s concept aboutsomething is the impact of the individual’s way of thinking about somethingbased on the culture containing non-individual but public meaning. So, whenthe system of meaning belongs to the collective society, society can have thesame pattern of behaviour. The cultural factors can serve as a basis forimproving urban residents' access to healthy latrines.